PENERAPAN NILAI DAN ETIKA DALAM INTERVENSI: Dilema Etis Pekerja Sosial Dalam Program Pemberdayaan Kelompok Pemulung Mardiko Piyungan Bantul - Khoniq Nur Afiah (UIN Sunan Kalijaga Yogyakarta, 2020)
Social workers have an obligation to apply values and ethics as a form of professionalism in the intervention process. However, in reality the application of values and ethics sometimes experiences ethical problems or dilemmas. The focus of research on the application of social worker values and ethics in the mentoring process to clients, especially in the community empowerment program for the Mardiko scavenger group at TPST Piyungan Bantul, Yogyakarta. As well, looking at the ethical dilemmas experienced by social workers while applying values and ethics. This research uses a qualitative-descriptive method of research and data collection techniques are carried out by interview methods, observation and documentation. The results of this study state that the application of values and ethics in the Mardiko scavenger empowerment program at TPST Piyungan includes acceptance, individualization, expression of taste, non-judgmental attitude, objectivity, self-determination and confidentiality. This study also explains that social workers in the practice of community empowerment mentoring experience ethical dilemmas such as when giving scavengers the freedom to determine their own destiny, but on the other hand this freedom has an inaccurate effect on scavengers in making choices. Another ethical dilemma that occurs relates to professional and personal values. but on the other hand, sthis freedom gives an inaccurate effect on scavengers in making choices. Another ethical dilemma that occurs relates to professional and personal values. but on the other hand, this freedom gives an inaccurate effect on scavengers in making choices. Another ethical dilemma that occurs relates to professional and personal values. Keywords: ethical dilemma, Social Workers, Seavengers